Methods for evaluating the impact of vertical programs on health systems: protocol for a study on the impact of the global polio eradication initiative on strengthening routine immunization and primary health care - Closser, Svea (BioMed Central, 2012)
BACKGROUND: The impact of vertical programs on health systems is a much-debated topic, and more evidence on this complex relationship is needed. This article describes a research protocol developed to assess the relationship between the Global Polio Eradication Initiative, routine immunization, and primary health care in multiple settings. METHODS/DESIGN: This protocol was designed as a combination of quantitative and qualitative research methods, making use of comparative ethnographies. The study evaluates the impact of the Global Polio Eradication Initiative on routine immunization and primary health care by: (a) combining quantitative and qualitative work into one coherent study design; (b) using purposively selected qualitative case studies to systematically evaluate the impact of key contextual variables; and (c) making extensive use of the method of participant observation to create comparative ethnographies of the impact of a single vertical program administered in varied contexts. DISCUSSION: The study design has four major benefits: (1) the careful selection of a range of qualitative case studies allowed for systematic comparison; (2) the use of participant observation yielded important insights on how policy is put into practice; (3) results from our quantitative analysis could be explained by results from qualitative work; and (4) this research protocol can inform the creation of actionable recommendations. Here, recommendations for how to overcome potential challenges in carrying out such research are presented. This study illustrates the utility of mixed-methods research designs in which qualitative data are not just used to embellish quantitative results, but are an integral component of the analysis.